Consideration of a New Simple Method of Evaluating Masticatory Efficiency by the Colored Gummy Jelly - Ikeda, Hiroichi; Watanabe, Megumi; Hayashida, Yukiko; Ichikawa, Tetsuo; Kitaoka, Naoki; Hada, Masaru; Nagao, Kan (Nihon Hotetsu Shika Gakkai Zasshi, 2004)
Purpose: Various prosthetic dentistry treatments are indispensable for patients who have a malfunction of mastication. In these circumstances, the objective assessment of mastication is very important for not only evaluating the treatment but also selecting diagnosis and treatment. The purpose of the current study is to design a simple assessment of mastication with colored gummy jelly, and to investigate the effectiveness of this method in comparison with Manly's sieving method and to discuss the development of this method (such as the possibility of visual assessment). Methods: Thirteen subjects who had no malfunction of mastication chewed the colored gummy jelly and the absorbance of the residual coloring matter after mastication was measured to assess their mastication in comparison with Manly's sieving method. Moreover, the absorbance of 5 gradations of color in test colored aqueous solutions was presumed with 9 gradations of color samples that were made as guidelines. Results: The higher the masticatory count was, the larger the values of mastication in both the sieving method and colored gummy jelly method were. The rate of increase decreased according to the increase of masticatory count in the sieving method, while the value of mastication in the colored gummy jelly method was proportional to the masticatory count. The value of mastication in the sieving method was proportional to the logarithm of absorbance. Regarding visual assessment, error and deviation were small when the absorbance of colored aqueous solution was less than 0.5. Conclusions: The value of mastication in the sieving method was proportional to the logarithm of absorbance. The colored gummy jelly method was as effective as Manly's sieving method when the masticatory count was less than 20 times. Moreover, it is supposed that masticatory efficiency can be determined by using this assessment.